Climate Change : Identification and Projections. - De Larminat, Philippe (Focus series., 2014)
Under certain scenarios on the subject of CO2 emissions, by the end of the century the atmospheric concentration could triple its pre-industrial level. The very large numerical models intended to anticipate the corresponding climate evolutions are designed and quantified from the laws of physics. However, little is generally known about these: genesis of clouds, terms of the greenhouse effect, solar activity intervention, etc. This book deals with the issue of climate modeling in a different way: using proven techniques for identifying black box-type models. Taking climate observations fr.